IMPROVEMENT OF INNOVATION ACTIVITY OF AN ENTERPRISE USING A MODEL “OPEN INNOVATIONS” - Olga I. Mitiakova; Nikolai A. Tolstopyatov (Статистика и экономика, 2016)
The article deals with the problem of realization of innovation activities using a model “closed innovations”, as well as using another way of development - a model “open innovation”. Advantages and disadvantages of these models are revealed. The authors analyze a state of food industry in view of Russia and the Nizhniy Novgorod Region and consider measures to improve the efficiency of innovation process in this branch.